(untitled) (Research, Society and Development, 2023)
Breastfeeding is essential for a child’s growth and development. It encompasses much more than just the act of feeding, the impact it has on preterm recovery is notable. The present study aimed to correlate exclusive breastfeeding with the development of premature newborns. Exclusive breastfeeding benefits in the prevention of diseases and psychomotor development, in the prevention of childhood obesity, among others. Breast milk is full of constituents that benefit the child in all aspects. This research will be carried out through a literature review, a selection of articles related to the topic will be made and articles that address breastfeeding, its benefits for the recovery of premature babies, its benefits for development during early childhood, studies that link childhood obesity with breastfeeding and important points about exclusive and complementary breastfeeding and properties of breast milk. It was found that more than 60% of mothers do not perform EBF for the ideal time and in the recommended way, often due to the milk that has dried up or stopped coming down, but also due to lack of time due to maternity leave and external factors. It is concluded that exclusive breastfeeding helps in the recovery of preterm newborns, helps in the adequate development and growth of the child and generates a positive impact on eating patterns and the functioning of human body systems.